Appropriate Needle Length Determined by Ultrasonic Echography for Intramuscular Injection in Japanese Elderly over 50 Years - Nakayama, Tetsuo; Sekino, Hisakuni; Aihara, Hirokazu; Kino, Minoru (Healthcare (Basel), 2022)
Adjuvanted vaccines are administered through intramuscular injection. To perform appropriate injection using an appropriate needle in different age groups or different daily living activities, we investigated the depth from the skin surface to muscle fascia and bone in the deltoid muscle area in 156 elderly aged ≥ 50 years by ultrasonic echography. Subjects consisted of 50 healthy elderly aged 50–64 years, 50 subjects aged 65–74 years, and 56 subjects aged ≥ 75 years (20 outpatients, 18 who needed nursing care, and 18 bedridden in a nursing home). The mean depth ± 1.0 SD from the skin surface to muscle fascia was 7.52 ± 2.13 mm for subjects aged ≥ 75 years, being shorter than 9.16 ± 3.02 mm in those aged 50–64years (p < 0.01). The depth from the skin surface to bone was 22.54 ± 3.85 mm for subjects aged ≥ 75 years and 25.41 ± 4.24 mm for those aged 65–74 years, significantly shorter than those aged 50–64 years (p < 0.01), depending on the reduced muscle volume. The subcutaneous volume length was greater in females (8.29 ± 2.63 mm) than in males (5.62 ± 2.80 mm) aged 50–64 years (p < 0.01). A similar result was obtained in those aged 65–74 years, but there was no difference in the muscle volume length. Our study found that a five-eighths of an inch (16 mm) needle was an appropriate length for average-sized elderly aged ≥ 50 years, but it should be longer for those with large body sizes.